Incidental finding of impacted supernumerary teeth in cone-beam computed tomography 3D - Putri Marina Sukmadewi; Anak Agung Gde Dananjaya Agung (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: To evaluate the value of cone-beam CT (CBCT) in the diagnosis and orientation of impacted supernumerary teeth in the dental arches. Case Report: A 50 year old man came to the Udayana University Hospital with the chief complaint of missing bilateral posterior teeth of the mandible and wanted to make denture. Before the treatment begin, a panoramic radiographic examination was performed. The panoramic image shows an impacted supernumerary teeth on the inferior from lower right premolar. Due to the inability to determine the precise position of those teeth within the mandible and the possible vital structures surrounding, a CBCT imaging was taken. Examination of the images from the CBCT shows an impacted supernumerary teeth in the area of teeth 44 and 46. Conclusion: The position of the supernumerary teeth is varied in the mandible, and often causes permanent dentition complications. In this case CBCT imaging two supernumerary teeth were found in the tooth area 44-45 and 45-46. apical of the two germ teeth appear to be fully formed. Supernumerary crowns between teeth 44-45 inclined buccally & between teeth 45-46 lingually. CBCT is crucial for exact localization, for treatment planning, and for the surgical approach in cases of multiple supernumerary teeth.